The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4314/njp.v43i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of asthma exacerbation in children seen at the University of Nigeria Teaching Hospital, Enugu

et al.

Abstract: Abstract:Background: Acute exacerbation is a major cause of morbidity in asthmatic children. It can occur even in well controlled asthma. Aim: To determine the prevalence and pattern of acute exacerbation of asthma in children seen at the emergency room of the University of Nigeria Teaching Hospital (UNTH), Enugu. Materials and methods:This was a descriptive, cross sectional study in which consecutive children with acute exacerbation of asthma presenting to the Children Emergency Room (CHER) of UNTH, Enugu wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
(27 reference statements)
7
8
0
Order By: Relevance
“…Nearly a three-quarter of our patients were admitted for ≤12 h probably due to most cases being mild asthma exacerbation. This is similar to the 74.6% of mild to moderate cases admitted for such short duration in another study from Nigeria ( Edelu et al, 2016 ). The short duration of admission by most of the patients may be a pointer to the efficiency of appropriate management plan instituted in all cases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nearly a three-quarter of our patients were admitted for ≤12 h probably due to most cases being mild asthma exacerbation. This is similar to the 74.6% of mild to moderate cases admitted for such short duration in another study from Nigeria ( Edelu et al, 2016 ). The short duration of admission by most of the patients may be a pointer to the efficiency of appropriate management plan instituted in all cases.…”
Section: Discussionsupporting
confidence: 89%
“…None of the patients presented with severe asthma exacerbations. This finding is surprising given the high rates reported in local and international studies ( Edelu et al, 2016 ; Dondi et al, 2017 ). A plausible explanation for this finding is that nearly all the patients were registered old patients of UDUTH; the only tertiary public hospital in the entire Sokoto State that runs a pediatric Pulmonology clinic.…”
Section: Discussionmentioning
confidence: 79%
“…Reported studies on exacerbations of childhood bronchial asthma in Nigeria showed that it may be responsible for about 2.9% to 6.5% of admissions into Children Emergency Units. [42,43] There were also reported peaks of exacerbations during the rainy seasons. [42,43] Unfortunately, the levels of knowledge of health care providers in the management of asthma exacerbation appears grossly suboptimal.…”
Section: Acute Asthmatic Exacerbations In Nigerian Childrenmentioning
confidence: 99%
“…[42,43] There were also reported peaks of exacerbations during the rainy seasons. [42,43] Unfortunately, the levels of knowledge of health care providers in the management of asthma exacerbation appears grossly suboptimal. [44] Fawibe, et al, [44] in a survey of the mode of management of asthma exacerbation among Nigerian doctors in private practice, observed that majority (83.6%) were not aware of any guideline, both local and global, hence there was the frequent use of "aberrant drugs" such as antibiotics, mucolytic agents and antihistamines in their treatment schedules.…”
Section: Acute Asthmatic Exacerbations In Nigerian Childrenmentioning
confidence: 99%
“…Asthma itself is a public health concern, being a major cause of infirmity, depletes scarce health resources and reduces quality of life of affected individuals. With its predisposition to dental caries formation in the affected individuals, the burden becomes more profound especially in developing countries like Nigeria, where health costs are largely borne by the individual patient [4,5].…”
Section: Introductionmentioning
confidence: 99%